From Narrative to Necessity : Meaning and the Christian Movement according to Hegel. - Theron, Stephen (Cambridge Scholars Pub., 2012)
This book is a supplement to the author's earlier New Hegelian Essays. It continues the project of presenting the narrative(s) of religion as intelligible metaphysics, "interpreting spiritual things spiritually", as St. Paul says. After an introductory recall of the unreality of the phenomenal individual except insofar as viewed as "in" God, the Absolute, so that all depend upon all, the first subject to be considered is faith itself, too often seen as the polar and hence negative opposite of ...